Randomised controlled trial in cadavers investigating methods for intubation via a supraglottic airway device: Comparison of flexible airway scope guided versus a retrograde technique. (27th November 2021) - Groombridge, Christopher J; Maini, Amit; Johnny, Cecil; McCreary, David; Kim, Yesul; Smit, De Villiers; Fitzgerald, Mark
Abstract: Objective: A supraglottic airway device (SAD) may be utilised for rescue re‐oxygenation following a failed attempt at endotracheal intubation with direct or video laryngoscopy. However, the choice of subsequent method to secure a definitive airway is not clearly established. The aim of the present study was to compare two techniques for securing a definitive airway via the in‐situ SAD. Methods: A randomised controlled trial was undertaken. The population studied was emergency physicians (EPs) attending a cadaveric airway course. The intervention was intubation through a SAD using a retrograde intubation technique (RIT). The comparison was intubation through a SAD guided by a flexible airway scope (FAS). The primary outcome was time to intubation. The trial was registered with ANZCTR.org.au (ACTRN12621000995875). Results: Four EPs completed intubations using both methods on four cadavers for a total of 32 experiments. The mean time to intubation was 18.2 s (standard deviation 8.8) in the FAS group compared with 52.9 s (standard deviation 11.7) in the RIT group; a difference of 34.7 s (95% confidence interval 27.1–42.3, P < 0.001). All intubations were completed within 2 min and there were no equipment failures or evidence of airway trauma. Conclusion: Successful tracheal intubation of cadavers by EPs is achievable, without iatrogenic airway trauma, via a SAD using either a FAS or RIT, but was 35 s quicker with the FAS. Abstract : Following a failed attempt at endotracheal intubation rescued with a supraglottic airway device (SAD) the choice of subsequent method to secure a definitive airway is not clearly established. This randomised controlled trial compared the time to tracheal intubation of a cadaver, via a SAD, using either a retrograde intubation technique or a flexible airway scope (FAS). Successful intubation is achievable via a SAD using either a FAS or retrograde intubation technique, but was 35 seconds quicker with the FAS.